Edupreneurship management in shaping the nation's character - Nurjaya Nurjaya; Akhmad Sobarna; Azhar Affandi; Heri Erlangga; Sarwani Sarwani (Jurnal Konseling dan Pendidikan, 2020)
The character cannot be directly obtained, it is instantaneous but requires time with the custom of academic habits to become a necessity and ultimately to get entrepreneurial skills, the purpose of identifying students' entrepreneurial skills in supporting the nation's character. Mix method with Convergence Model and t-test analysis shows that there are differences in indicators of student entrepreneurial skills with character education treatment and those that are not. There is the lowest indicator on creative thinking and responding to global problems by 60% enough categories. so it needs to be improved in further research with edupreneurship designs that are characterized in preparation, teaching materials, resources and learning media that are adapted to technological developments.